Terapi Kombinasi Terhadap Nyeri Akut Abdomen di RSUD Bangil Kabupaten Pasuruan Jawa Timur - Dian Ratna Elmaghfuroh; Yuyud Wahyudi (Borneo Journal of Medical Laboratory Technology, 2019)
Nurses have important role to handling and controlling pain of the patient. The combination of pain management with appropriate therapy or non-pharmacological therapy were the key to decreasing pain intensity. This research aimed to determine the effect of analgesic theraphy and lavender aromatherapy compared with analgesic therapy and relaxation on decreased the level of abdominal pain in adult patients in Emergency Room, Bangil District Hospital, Pasuruan, East Java. This research was utilized quasi experimental design with non-equivalent control group design. The intervention was carried out on 28 respondent has been selected by purposive sampling. Ethical approval in this study was carried out through training department of Bangil District Hospital and the distribution of informed consent to patients. Both types of deep breathing relaxation therapy and lavender aromatherapy combined with pharmacological (analgesic) has showed effectiveness in decreasing the level of acute abdominal pain in Emergency Room in Bangil Distric Hospital, Pasuruan, East Java. In the future, it should be considered the use of lavender aromatherapy method as an alternative step of care and treatment in patients who experience acute abdominal pain